The interaction between rumination and job embeddedness among trainee nurses during internship: A multicenter longitudinal study - Weiyi Wang; Huizhen Ma; Lei Huang; Chen Ying (PLoS ONE, 2026)
Objective To explore the developmental trajectory of rumination and job embeddedness among college trainee nurses and examine the predictive relationship between them, with the aim of providing a theoretical basis for improving trainee nurses’ job embeddedness. Design A longitudinal study. Methods A total of 405 nursing interns from 12 colleges and universities in China were selected as the survey subjects. They were tracked using the Ruminative Responses Scale (RRS) and the Global Job Embeddedness Items (GJEI) at three time points: T1 (initial stage of internship, 1–2 months), T2 (middle stage of internship, 5–6 months), and T3 (completion of internship, 9–10 months). A cross-lagged model was constructed to analyze the causal relationship between the two variables. Results A total of 382 valid questionnaires were collected, yielding an effective response rate of 94.32%. In analyzing the overall trend from T1 to T3, rumination significantly decreased from a baseline of (44.79 ± 5.28) to (41.61 ± 5.27) (F = 47.360, P < 0.001). Concurrently, the score of job embeddedness increased significantly from (22.42 ± 4.89) to (25.48 ± 4.60) (F = 25.690, P < 0.001). The level of rumination at a previous time point negatively predicted job embeddedness at the subsequent point (β = −0.403, P < 0.01; β = −0.411, P < 0.001), and job embeddedness at a previous time point negatively predicted rumination at the next point on average (β = −0.397, P < 0.001; β = −0.385, P < 0.001). At the initial level, rumination can predict job embeddedness negatively (β = 0.433, P = 0.002), the initial level of rumination can predict the development speed of job embeddedness negatively (β = 0.395, P = 0.005), and the development speed of rumination can positively predict the development speed of job embeddedness (β = 0.450, P < 0.001). Conclusion practice trainee nurses rumination is on the decline, job embeddedness is on the rise. Educators and clinical instructors should assess and monitor rumination levels in trainee nurses and strategically leverage the dynamic relationship between rumination and job embeddedness to enhance the latter during clinical training.